Cardio-Oncology rehabilitation- challenges and opportunities to improve cardiovascular outcomes in cancer patients and survivors. Issue 6 (December 2020) - Sase, Kazuhiro; Kida, Keisuke; Furukawa, Yutaka
Highlights: Cardio-Oncology is an emerging interdisciplinary field to support cancer survivors. Cardio-Oncology Rehabilitation is a comprehensive approach to improve cancer outcomes. Cancer patients with cardiovascular risk factors are likely to benefit from exercise. Cancer Treatment-Related Cardiovascular Disorders may be reduced with rehabilitation. Limitations associated with disease and treatment may require cancer rehabilitation. Summary: While the number of cancer patients is increasing with the arrival of the super-aging society, the age-adjusted mortality rate of cancer decreases due to medical advances, and the number of cancer survivors is growing rapidly. Cardiovascular disease (CVD) is one of the most important causes of death among cancer survivors. In recent years, the number of cancer patients with CVD risk factors has increased. Also, the emergence of new drugs has led to the emergence of a new condition called cancer treatment-related cardiovascular disease (CTRCD). Cardio-oncology (onco-cardiology) is a new multidisciplinary field with the common goal of completing cancer treatment and improving the prognosis of cancer patients and survivors, including the prevention, diagnosis, and treatment of CTRCD. Cardio-oncology rehabilitation (CORE) is a new concept that aims to reduce the risk of CVD and improve cardiopulmonary fitness in cancer survivors by providing exercise prescriptions and cardiac rehabilitation in addition to so-called cancer rehabilitation during and after cancer treatment. This review provides an overview of the theoretical background, feasibility, challenges, and opportunities of CORE, including a series of recent white papers and scientific statements released by the American Heart Association.